Biological functions and applications of rosemary extracts in animal production - Liu, Z.; Xia, T.; Jiang, A.; Zhou, C.; Lukuyu, Ben A.; Tan, Z. (Chinese Association of Animal Science and Veterinary Medicine, 2026)
Rosemary (Rosmarinus officinalis L.) is renowned for its wide array of bioactive compounds, such as phenolic acids, terpenoids, and flavonoids. Alongside its role as a natural antioxidant, rosemary extract demonstrates anti-inflammatory, antimicrobial, and growth-promoting effects, making it a promising feed supplement for sustainable animal production. Recent research has highlighted its potential to enhance rumen fermentation, improve meat quality, and bolster immune responses in various livestock and poultry species. In dairy cattle, supplementation with rosemary extract elevates milk nutritional quality and antioxidant levels while decreasing methane emissions during rumen fermentation. However, much of the current literature focuses on mixed extracts or in vitro models, with limited exploration of its specific in vivo mechanisms of action. This review systematically outlines recent advances in rosemary extract research, emphasizing its biological functions and practical applications in livestock and poultry production. Challenges related to standardizing its chemical composition and characterizing its functionality are discussed, along with suggestions for future studies utilizing omics technologies to elucidate its mechanisms and optimize its utility as a plant-derived feed additive.